Pollution trends over Europe constrain global aerosol forcing as simulated by climate models. Issue 6 (19th March 2014) - Cherian, Ribu; Quaas, Johannes; Salzmann, Marc; Wild, Martin
<x xml:space="preserve">Abstract</x> An increasing trend in surface solar radiation (solar brightening) has been observed over Europe since the 1990s, linked to economic developments and air pollution regulations and their direct as well as cloud‐mediated effects on radiation. Here, we find that the all‐sky solar brightening trend (1990–2005) over Europe from seven out of eight models (historical simulations in the Fifth Coupled Model Intercomparison Project) scales well with the regional and global mean effective forcing by anthropogenic aerosols (idealized "present‐day" minus "preindustrial" runs). The reason for this relationship is that models that simulate stronger forcing efficiencies and stronger radiative effects by aerosol‐cloud interactions show both a stronger aerosol forcing and a stronger solar brightening. The all‐sky solar brightening is the observable from measurements (4.06±0.60 W m−2 decade−1), which then allows to infer a global mean total aerosol effective forcing at about −1.30 W m−2 with standard deviation ±0.40 W m−2.